Analisis Saluran Pemasaran Buah Duku Di Desa Selensen Kecamatan Kemuning Kabupaten Indragiri Hilir - Amina, Siti (Universitas Medan Area, 2023)
The purpose of this study was to determine the duku fruit marketing channel, and the marketing margin of duku fruit in Selensen Village, Kemuning District, Indragiri Hilir. In this study, the population consisted of 25 duku farmers, 2 collectors, and 3 traders. So that the entire population is used as a sample in this study. This research was conducted in Selensen Village, Kemuning District, Indragiri Hilir Regency. The data used in this study are primary data and secondary data. The data analysis technique used is the formula M = Hp – Hb to calculate marketing margins. The results showed that there were two marketing channel patterns for duku fruit in Selensen Village, Kemuning District, namely marketing channel I: Farmers - Collectors - Retailers - Final Consumers and marketing channel II: Farmers - Final Consumers. For the highest marketing margin obtained by farmers in marketing pattern II with a marketing margin of Rp. 11,700/Kg, while the smallest marketing margin is obtained by traders with a value of Rp. 2,900/Kg.